2020
DOI: 10.3390/su12218888
|View full text |Cite
|
Sign up to set email alerts
|

Online Recommendation Systems: Factors Influencing Use in E-Commerce

Abstract: The increasing use of artificial intelligence (AI) to understand purchasing behavior has led to the development of recommendation systems in e-commerce platforms used as an influential element in the purchase decision process. This paper intends to ascertain what factors affect consumers’ adoption and use of online purchases recommendation systems. In order to achieve this objective, the Unified Theory of Adoption and Use of Technology (UTAUT 2) is extended with two variables that act as an inhibiting or posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Marinkovic and Kalinic [31], Singh et al [36], Do et al [75], and Humbani and Wiese [76] reported positive correlations between perceived utility and consumer satisfaction in the process of adoption of e-commerce and mobile payments. Although several studies [64,70,72] have reported a strong correlation between perceived utility and m-commerce use, they did not focus on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Marinkovic and Kalinic [31], Singh et al [36], Do et al [75], and Humbani and Wiese [76] reported positive correlations between perceived utility and consumer satisfaction in the process of adoption of e-commerce and mobile payments. Although several studies [64,70,72] have reported a strong correlation between perceived utility and m-commerce use, they did not focus on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In empirical research, most TAMbased studies use the following antecedent variables for the two variables (PEU and PU): confidence, innovation, mobility, enjoyment, and social influence [30][31][32][66][67][68][69][70][71]. Some studies used customer satisfaction as a variable in TAM to determine the influence on consumer adoption of m-commerce [29][30][31][35][36][37][38][39][40][41][42][43][44][45][72][73][74][75][76][77][78]; exploring consumer behavioral intent and customer satisfaction. Our study used a simplified TAM model, in which consumer satisfaction influences behavioral intention.…”
Section: Research Design and Hypothesismentioning
confidence: 99%
See 3 more Smart Citations